To what extent do community members participate in planning, implementing health programs within their communities and what are the benefits of their participation in Nigeria? - Ojielo, Nwadiuto Chidinma; Etiaba, Enyinnaya; Onwujekwe, Obinna (International Journal Of Community Medicine And Public Health, 2024)
Background: Community participation in health programs helps drive collaborations between the formal health structures and informal health system actors in promoting health at the community level. This paper provides new information on the extent of community participation in the planning and implementation of community-based health programs in Nigeria as a trajectory for strengthening the health system. Methods: This was a qualitative study. Data was collected from three located in different geographic zones of Nigeria. Two local governments (rural and urban) with evidence of health programs were purposively selected in each state. Data were collected through in-depth interviews and focus group discussions. The data was transcribed, coded manually and analysed thematically. Results: Several health programs were identified in the community. It was found that while community leaders are hardly involved in conceptualizing and planning health programs, however, they participate in program implementation by mobilizing community resources and encouraging members to take advantage of available health activities. Our findings also showed increased benefits of the involvement of the informal health workers in the health system. Conclusions: Community participation and involvement in health as part of community health system (CHS) activities has led to better and well-improved services, increased willingness to access immunization services. Communities are readily available to contribute to health activities, but they should be involved in the initiation and planning of health activities for ownership and full participation. This would improve health outcomes and contribute to strengthening the community health system.